5y-7 = 2y+11 (+7 to both sides)
5y = 2y+18 (- 2y from both sides)
3y = 18 (divide both sides by 3 )
y = 6
y=6
Chat with our AI personalities
x = 11 - 2y and 14 - 2y. This means that 11 = 14. Is there a typo in the question?
(-1, 2)
This means that 2y - 3 = 2y + 4 which is not possible.
2y+26 = 28 2y = 28-26 2y = 2 y = 1
To solve this, you would normally set up a systems of equations 10x + 2y = 10 10x + 2y = 11 However, it clearly makes no sense and has no answer. To prove this mathematically, subtact the two equations. 10x - 10x = 0 2y - 2y = 0 10-11 = -1 Therefore, it is basically saying that 0 + 0 = -1 Obviously, that is incorrect, so this question has no solutions.